Thymosin alpha 1 in the prevention of infected pancreatic necrosis following acute necrotising pancreatitis (TRACE trial): protocol of a multicentre, randomised, double-blind, placebo-controlled, parallel-group trial - Tao Chen; Jing Zhou; Jianfeng Tu; Weiqin Li; XinTing Pan; Wenjian Mao; Lu Ke; Wenhua He; Miao Chen; Chengjian He; Weili Gu; Jingyi Wu; et al. (BMJ Open)
Introduction Infected pancreatic necrosis (IPN) and its related septic complications are the major causes of death in patients with acute necrotising pancreatitis (ANP). Therefore, the prevention of IPN is of great clinical value, and immunomodulatory therapy with thymosin alpha 1 may be beneficial. This study was designed to test the hypothesis that the administration of thymosin alpha 1 during the acute phase of ANP will result in a reduced incidence of IPN.Methods and analysis This is a randomised, multicentre, double-blind, placebo-controlled study. 520 eligible patients with ANP will be randomised in a 1:1 ratio to receive either the thymosin alpha 1 or the placebo using the same mode of administration. The primary endpoint is the incidence of IPN during the index admission. Most of the secondary endpoints will be registered within the index admission including in-hospital mortality, the incidence of new-onset organ failure and new-onset persistent organ failure (respiration, cardiovascular and renal), receipt of new organ support therapy, requirement for drainage or necrosectomy, bleeding requiring intervention, human leucocyte antigens-DR(HLA-DR) on day 0, day 7, day 14, and so on and adverse events. Considering the possibility of readmission, an additional follow-up will be arranged 90 days after enrolment, and IPN and death at day 90 will also be served as secondary outcomes.Ethics and dissemination This study was approved by the ethics committee of Jinling Hospital, Nanjing University (Number 2015NZKY-004-02). The thymosin alpha 1 in the prevention of infected pancreatic necrosis following acute necrotising pancreatitis(TRACE) trial was designed to test the effect of a new therapy focusing on the immune system in preventing secondary infection following ANP. The results of this trial will be disseminated in peer-reviewed journals and at scientific conferences.Trial registration number ClinicalTrials.gov Registry (NCT02473406).